2011
DOI: 10.1097/shk.0b013e31822f7e58
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Increases Susceptibility to Endotoxin Shock Through Enhanced Release of High-Mobility Group Box 1

Abstract: High-mobility group box 1 (HMGB1) is a nuclear factor and a secreted protein. During inflammation, HMGB1 is secreted into the extracellular space where it can interact with the receptor for advanced glycation end products and trigger proinflammatory signals. Extracellular HMGB1 plays a critical role in several inflammatory diseases such as sepsis and rheumatoid arthritis. Valproic acid (VPA) is one of the most frequently prescribed antiepileptic drugs. The present study was undertaken to investigate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…4 ). The resistance of IXR1 null mutant which encodes an HMG domain-containing protein to VA is in accordance with an earlier study that shows VA exacerbate innate immune responses to endotoxin by enhancing the release of High-mobility group box-1 (HMGB1) 47 . Altogether, our results demonstrated that VA mediates its toxicity through alteration of genomic stability, redox and lipid homeostasis, ER and mitochondrial functions.…”
Section: Discussionsupporting
confidence: 90%
“…4 ). The resistance of IXR1 null mutant which encodes an HMG domain-containing protein to VA is in accordance with an earlier study that shows VA exacerbate innate immune responses to endotoxin by enhancing the release of High-mobility group box-1 (HMGB1) 47 . Altogether, our results demonstrated that VA mediates its toxicity through alteration of genomic stability, redox and lipid homeostasis, ER and mitochondrial functions.…”
Section: Discussionsupporting
confidence: 90%
“…36,37 On the other hand, HMGB1 has also been reported to be a substrate for histone acetylase, and HDAC inhibitors can increase the release and relocation of HMGB1 from the nucleus to the cytoplasm. 3840 In this study, we detected an increase in HMGB1 in the VPA treated group (Fig 8). It could be a “side effect” of VPA, although the VPA treatment exhibited an overall neuroprotective effect.…”
Section: Discussionsupporting
confidence: 59%
“…In contrast, VPA can exacerbate the RAW264.7 macrophage response to LPS by increasing the release of the nuclear factor HMGB1, which associates with the promotion of inflammatory processes. This effect is mediated by an increase in the expression of the GABA receptor, leading to phosphorylation of the transcription factor ERK1/2, without promoting either p38 or c-JUN phosphorylation [62].…”
Section: Effects Of Valproic Acid On Cells Of the Innate Immune Rementioning
confidence: 99%